Evaluasi Implementasi Analisis Kesebandingan atas Sengketa Transfer Pricing PT OCI - Rafael Tambunan; Yulianti Abbas (Owner : Riset dan Jurnal Akuntansi, 2023)
Transfer pricing is one of the most popular drivers of tax disputes between taxpayers and tax authorities around the world. To lessen the probability of disputes, the OECD proposes procedures for comparability analysis. These procedures help taxpayers and tax authorities to determine the arm's length values of related-party transaction, which is the main cause of many transfer pricing disputes. This study uses a case study method, focusing on PT OCI, to evaluate a firm’s comparative analysis practice and its conformity to OECD Transfer Pricing Guidelines. Data collection through interviews and documentation. The results of this study indicate that PT OCI had conducted a comparability analysis of transfer pricing transactions in conformity with the OECD guidelines, while the tax authorities have not carried out a comparability analysis in carrying out transfer pricing audits. However, specifically for trademark utilization transactions, PT OCI must accept the results of inspection corrections. Fulfillment of the arm’s length principle for transactions utilizing intangible assets must comply with two additional provisions, namely related to the existence of transactions and economic benefits from the utilization of intangible assets. With the results of the benefit test, it was concluded that the trademark used by PT OCI did not contribute to increasing the success of PT OCI's sales so that transactions for the use of intangible assets did not meet the arm’s length principles.